Physiotherapy performance in palliative care in oncological patients: An integrative review (Research, Society and Development, 2021)
The oncology physiotherapist plays a role in preventing, treating and palliating dysfunctions at any time during cancer treatment, such as in diagnosis, pre, peri and post-surgery, in the effects of treatments such as chemotherapy, radiotherapy, hormone therapy, immunotherapy or even in exclusive palliative care. This study aimed to analyze the scientific productions regarding the performance of physiotherapy in palliative care in cancer patients. This is an integrative review bibliographic search, with the following guiding question: What is the importance of the physiotherapist's performance in palliative care in cancer patients? Descriptors were used and the databases consulted were: Latin American and Caribbean Literature on Health Sciences (LILACS); Scientific Electronic Library Online (SCIELO) and Medical Literature Analysis and Retrieval System Online (Medline). The final sample of studies selected from the databases was composed of 12 scientific articles, taking into account the inclusion and exclusion criteria established in this study, in which they were extracted directly from the databases, and assessed for eligibility to answer the guiding question. proposed in the research. The study sought through the scientific literature to understand the role of the physiotherapist in palliative care. This professional has a fundamental role as a member of the multidisciplinary team and in the monitoring of cancer patients, as physiotherapy has an extensive area of ​​knowledge that can be used and put into practice for the development of care plans in the care provided to cancer patients.